Pengaruh School Climate dan Procedural Justice terhadap Citizenship Behavior towards Environment Siswa SMA - I Made Putrawan; RefirmanDj; Yulianita Tri Jayanti (IJEEM - Indonesian Journal of Environmental Education and Management, 2021)
Environmental destruction that occurs in Indonesia is increasing due to weak awareness behavior in protecting the environment. One of the efforts that can be made with citizenship behavior toward environment. This study aims to determine the influence of school climate and procedural justice on citizenship behavior toward environment. The method used is a survey method through causal studies and analyzed by path analysis. This research was conducted towards 70 students in SMAN 68 Jakarta in the odd semester of the 2020/2021 school year. The result of relianility coefficient calculation of citizenship behavior toward environment was 0.802, procedural justice was 0.786, and school climate was 0.930. The results showed that school climate had a significant direct effect on procedural jsutice, procedural justice had a significant direct effect on citizenship behavior toward environment, school climate had a significant direct effect on citizenship behavior toward environment, and obtained good procedural justice results as a mediator variable between school climate and citizenship behavior toward environment in students